Community Colleges Mobilization with Strengthening of Youth and Local Resources Utilization for Sustainable Development: A Review - Ghimire , Mayanath; Mishra, Anjay Kumar (International Research Journal of MMC, 2025)
To find review and study communion college mobilization with strengthening of youth and local resources utilization for sustainable development. The study employed the method of scientific review as a meta-synthesis to find a solution for the utilization of youth and local resources for the sustainable development of local colleges at the community level. In this review, the researcher primarily used deductive logical reasoning; however, the researcher’s observational experiences led to the arrangement of inductive logical reasoning during inference limited to adductive reasoning in a singular sense for achieving the completeness of the objective. Comprehensive archival analysis accompanied by a thorough review were strategies utilized during the scientific review. Provide part-time jobs during the university-level study time in Nepal. Support market-driven production, financial support for entrepreneur establishment, and link with marketing. Entrepreneurs focus on locally available raw materials. Create employment opportunities for qualified and young human manpower. Focus on learning and earning programs in each and every community college in Nepal and provide opportunities for earning, learning, and developing confidence levels. Production market-driven product and link with marketing.